Analysis of errors in spoken production of french L3 learners of level A2 at a private school in Quito - Erazo Jiménez, Rodrigo Javier (2021)
The present study deals with the issue of exploring the possible sources for the most frequent errors in oral production of teenage learners of French who are Spanish native speakers and have also received instruction in English. To attain this objective, online oral interactions of 15 students of a private school of Quito and their teacher in an interview-like setting have been transcribed and analyzed in search of errors. The quantitative data evidenced the most frequent ones which subsequently underwent a qualitative analysis. It consisted of a description of the errors and ultimately, a formulation of hypotheses on their possible causes. The results show that the most frequent types of erroneous production have to do with form rather than content and do not represent a major impediment to communication. As for their causes, the detected errors seem to have their origin not only on the interference of the first or second language, but also on overgeneralization and oversimplification of the rules of the target language. The existence of a combination of several features or sources was also deemed possible.